Evidence of Leishmania spp. antibodies and DNA in bush dogs (Speothos venaticus) in Brazil - Felix Lima, Valeria Marcal [UNESP]; Fattori, Karina Reinaldo [UNESP]; Michelin, Aparecida de Fatima [UNESP]; Nogueira, Fabio dos Santos [UNESP]; de Oliveira e Souza, Lucio (Amer Assoc Zoo Veterinarians, 2009)
The municipality of Ilha Solteira, São Paulo, Brazil is an endemic area of leishmaniasis. At the Companhia Energetica de São Paulo (CESP) Wild Animal Center of Ilha Solteira, two bush dogs (Speothos venaticus) showed clinical signs of this disease. The amastigote form of Leishmania was detected in lymph-node smears taken by fine-needle biopsy. In addition, serum samples from both animals, screened with an enzyme-linked immunosorbent assay (ELISA). were positive for anti-Leishmania antibodies. Moreover, tissue samples from one of the bush dogs were evaluated for the presence of Leishmania DNA by means of a polymerase chain reaction (PCR). DNA of the parasite was indeed detected in the tissue samples of the liver and the lymph nodes; however, no DNA from the parasite was detected in samples of the skin and spleen. These findings confirm a Leishmania infection in bush dogs (S. venaticus).
Keywords: bush dog; ELISA; Leishmania spp.; PCR; Speothos venaticus